Prenatal Gentle Yoga on Reducing Complaints of Discomfort in Trimester III Pregnant Women at Klinik Ananda Medika, 2022 - Nida Handayani; Lili Anggraini (STIKep PPNI Jawa Barat, 2023)
Aims: Pregnancy can cause physical and psychological changes, particularly in the third trimester, causing discomfort. Preventing these issues can be achieved through exercise, such as morning walking, static cycling, aerobics, water gymnastics, and dancing. Prenatal Gentle Yoga is a popular method for promoting good health and a normal delivery process. Objective: To determine the effect of Prenatal Gentle Yoga on Reducing Discomfort Complaints in Third Trimester Pregnant Women at Klinik Ananda Medika in 2022. Methods: The research design used in this study was a pre-experimental research method with a one group pretest and posttest design approach, namely a research design using one observation group before and after the experiment. Where the mother has never attended a Prenatal Gentle Yoga class the mother feels uncomfortable with her third trimester pregnancy (pretest) and after the mother attends the Prenatal Gentle Yoga class for 1 hour 2x a week for 4x and the mother feels comfortable (post test). Results: Based on the results of the pretest, it was found that 11 respondents (73.33%) had moderate complaints and 4 respondents had moderate and severe complaints and after Prenatal Gentle Yoga there were 10 respondents (66.67%) were pregnant women who had complaints mild discomfort, 5 respondents (33.33%) were pregnant women who experienced moderate complaints, and there were no severe categories. Based on the data above and according to the results of the Wilcoxon statistical test, a significant number or probability value (0.001) is much lower than the significant standard of 0.05 or (p <α), then Ho is rejected and Ha is accepted, which means that there is an effect before and after the Prenatal Gentle class. Yoga at Klinik Ananda Medika. Conclusion: Based on the results of a study of 15 respondents who had done Prenatal Gentle Yoga with at least 4 class meetings, it showed that pregnant women in their third trimester had complaints of pregnancy discomforts such as frequent urination, shortness of breath, back pain, heartburn, constipation, insomnia, discomfort in the perineum, calf muscle cramps, varicose veins, ankle edema, fatigue, erratic moods, and increased anxiety indicate that the complaints are felt to be milder and even non-existent.